Aqueous root extract of Asparagus cochinchinensis (Lour.) Merr. Has antioxidant activity in D-galactose-induced aging mice - Linghua Lei; Yanhua Chen; Lijun Ou; Yinglong Xu; Xiaoying Yu (BMC, 2017)
Abstract Background Extracts of plants have been considered as sources of natural antioxidant agents. In this study, we aimed to explore the antioxidant capacity of the aqueous root extract of Asparagus cochinchinensis (Lour.) Merr. Methods Using vitamin C (Vc) as a positive control, we analyzed the aqueous root extract of A. cochinchinensis free radical scavenging ability in vitro. We also established a mouse aging model using D-galactose and then treated it with aqueous root extract or Vc. The blood cell count and superoxide dismutase (SOD), catalase (CAT), and nitric oxide synthase (NOS) activities as well as malondialdehyde (MDA) and nitric oxide (NO) contents were measured; pathological examination of tissues was performed; and SOD, glutathione peroxidase (GPX), and NOS expression levels in the serum, liver, and brain tissues were investigated. Results In vitro, compared with the antioxidant Vc, the aqueous root extract showed similar 1,1-Diphenyl-2-picrylhydrazyl radical and 3-ethylbenzothiazoline-6-sulfonic·scavenging activities and even significantly increased superoxide anion (p < 0.05) and hydroxyl radical (OH) (p < 0.01) scavenging activities. The aqueous extract significantly increased the white blood cell count as well as enhanced SOD, CAT, and NOS activities (p < 0.01) in aging mice. In addition, the aqueous extract increased the NO content (p < 0.05) and reduced the MDA content (p < 0.05). Conclusions The aqueous root extract of A. cochinchinensis showed as strong antioxidant ability as Vc and might prevent aging by reducing radicals.